Improvisation and Radical Objectivization Identities in Angela Carter's The Bloody Chamber: A Lacanian Reading - Thulfiqar Abdulameer Sulaiman Alhmdni (Randwick International of Social Science Journal, 2023)
This research applies Lacanian psychoanalysis to scrutinize the use of improvisation and radical objectivization in Angela Carter's The Bloody Chamber. Drawing on Lacan's theory of the "mirror stage," the work argues that Carter's use of these literary techniques disrupts the reader's sense of identity and challenges their preconceived notions of self and other. Through close analysis of key passages from the text, the research demonstrates how Carter's use of these techniques creates a sense of alienation and fragmentation in the reader, as they are forced to confront the unsettling and often disturbing aspects of the stories. The work also explores how Lacan's concept of the "phallus" is invoked in Carter's work, as she challenges traditional gender roles and subverts the dominant male gaze through the use of powerful female protagonists. Further, it maintains that Carter's use of these techniques, offers a powerful critique of patriarchal norms and invites the reader to engage with the complex and often contradictory nature of identity and desire. By disrupting traditional fairy tale tropes and challenging patriarchal norms, Carter invites the reader to engage with the complex and often unsettling nature of identity and desire, and offers a powerful critique of the ways in which these concepts are shaped and constructed by dominant cultural narratives.